Observation of Rapid Seabed Erosion Near Closure Depth During a Storm Period at Hujeong Beach, South Korea - Jong Dae Do; Jae‐Youll Jin; Weon Mu Jeong; Yeon S. Chang (Geophysical Research Letters)
Abstract We report extraordinary seabed erosion that occurred at a depth of ~8.3 m at Hujeong Beach, South Korea. The seabed was eroded for 0.7 m during a ~2.3‐day period under storm conditions. The maximum significant wave height was ~3.8 m, which was unexpected considering the traditional closure depth concept. Four storm events were recorded within 36 day of the experimental period, but the severe erosion only occurred during the first storm. The erosion started when the nearbed flow velocity rapidly increased to reach its maximum at 0.27 m/s, and it continued until this velocity remained at its maximum. Additional factors responsible for the unanticipated erosion process were the current and wave skewness. The erosion was facilitated when the current direction was actively changing and the magnitude of positive skewness increased during the storm period. These factors are likely to have intensified the nearbed flow turbulence and bed shear stress.